2019
DOI: 10.14740/jocmr3670
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salivary Nitric Oxide Levels in Elite University Athletes in Japan: Findings From a Cross Sectional Study Design

Abstract: BackgroundHigh-intensity exercise affects the level of salivary nitric oxide (NO) with an impact on oxidative stress such as a reactive nitrogen-oxide species. However, in athletes with high-intensity training, the relationship between salivary NO levels and oxidative stress is yet to be clear. Additionally, the association of salivary NO levels and the common health disorders of athletes is unknown. Thus, the aim of this cross-sectional study was to clarify the relationship between salivary NO levels and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Finally, it is necessary to examine the validity of the method for quantifying s-NO in future studies. Although there are previous studies that determined s-NO by the same sample preservation method as the present study, their validity has not been examined in detail 10,15,31) . In the determination of s-NO, it should be examined whether the amount of NO can be accurately measured in the frozen preservation samples.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, it is necessary to examine the validity of the method for quantifying s-NO in future studies. Although there are previous studies that determined s-NO by the same sample preservation method as the present study, their validity has not been examined in detail 10,15,31) . In the determination of s-NO, it should be examined whether the amount of NO can be accurately measured in the frozen preservation samples.…”
Section: Discussionmentioning
confidence: 94%
“…s-SIgA is reported to be useful as a predictive biomarker that reflects URTI during highintensity training in many types of sports 8,9) . In contrast, salivary nitric oxide (s-NO) may reflect lower-respiratory tract inflammatory conditions such as asthma 10) . It is suggested that NO and nitrite formed in the oral cavity, such as s-NO, influence the oxidative stress as a reactive ni-trogen oxide species [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The d-ROMs values were 264 ± 34 U.CARR, BAP values were 2036 ± 145 µmol/L, BAP/d-ROMs ratio were 7.9 ± 1.2 in Study 1′ all subjects. In Sone’s study, Japanese elite male university athletes had a d-ROMs value of 271 ± 42 U.CARR, BAP value of 2154 ± 143 µmol/L and BAP/d-ROMs ratio of 8.13 ± 1.27 [ 25 ]. The BAP/d-ROMs ratio was slightly lower in our study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…If we evaluate their dietary intake and supplement intake, measure actual kiwifruit ingested, vitamin C and vitamin E in blood, we can discuss vitamin C and vitamin E more clearly. Moreover, women were reported to have higher d-ROMs than men did [ 25 , 30 ]. Thus, women may produce different results than those of men.…”
Section: Discussionmentioning
confidence: 99%
“…Serum derivatives of reactive oxygen metabolites (d‐ROMs), which are markers to evaluate hydroperoxide levels (oxidative stress), and serum biological antioxidant potential (BAP), which indicates antioxidant capacity, were measured using a FREE Carrio Duo (Wismerll Co., Ltd., Tokyo, Japan). The BAP/d‐ROMs ratio was also measured to evaluate serum oxidant‐antioxidant balance (Sone et al ). Blood lactate concentration was determined using a Biosen S‐Line (EKF‐diagnostic GmbH, Barleben, Germany) from 20 µ L of fingertip capillary blood sample.…”
Section: Methodsmentioning
confidence: 99%